EFFECTIVENESS OF TRIPLOIDIZATION ON INGIR-INGIR (Mystus nigriceps) WITH DIFFERENT FERTILIZATION AND HEAT SHOCK - Haloho, Mei Dinar Tauriska; Riauwaty, Morina; ', Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in August until November 2015 in the Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine Sciences, University of Riau, Pekanbaru. This research was aimed to know the triploidization effectiveness in fertilized egg of ingir-ingir larvae (Mystus nemurus) with different fertilization and heat shock. The method used in this research was the experimental method; 2 factors, 10 treatments and 3 replications. Fresh eggs and milt were fertilization, then 1, 2 and 3 minutes after fertilization zygotes were shocked by heat shock 400C for 1, 2 and 3 minutes. The treatments were, P0K0 (as control), P1K1, P1K2, P1K3, P2K1, P2K2, P2K3, P3K1, P3K2, P3K3. The result shown that the best results in treatment Fertilization Rate (P3K1=31,06%), Hatching Rate (P2K1=65,74%), Survival Rate of 4 days and Survival Rate of 21 days (P3K3=71,82% and 41,67%), the length and width of a red blood cell were (0.192 mm and 0.123 mm).Key Words: Triploidization, Mystus nemurus, Old Fertilization, Old Surprise, Heat Shock